Patient-reported outcomes in patients with relapsed or refractory follicular lymphoma treated with zanubrutinib plus obinutuzumab versus obinutuzumab monotherapy: results from the ROSEWOOD trial - Trotman, Judith; Zinzani, Pier Luigi; Song, Yuqin; Delarue, Richard; Kim, Pil; Ivanova, Elena; Korde, Rasika; Mayer, Jiří; De Oliveira, Ana C; Assouline, Sarit E; Flowers, Christopher R; Barnes, Gisoo (Current medical research and opinion, 2024)
OBJECTIVE: We report patient-reported outcomes (PROs) measuring health-related quality of life (HRQoL) from the ROSEWOOD trial (NCT03332017), which demonstrated superior efficacy and a manageable safety profile with zanubrutinib plus obinutuzumab (ZO) versus obinutuzumab (O) in patients with heavily pretreated relapsed/refractory follicular lymphoma (R/R FL). METHODS: PROs were assessed using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire - Core 30 (EORTC QLQ-C30) and EQ-5D-5L questionnaires at baseline and subsequently every 12 weeks. All QLQ-C30 domains and EQ-5D-5L visual analog scale (VAS) scores were analyzed descriptively. At the key clinical timepoints (weeks 12 and 24), a mixed model for repeated measures (MMRM) analysis was used to evaluate the key PRO endpoints, including global health status, physical and role functioning, and symptoms of fatigue, pain, diarrhea, and nausea/vomiting. Clinically meaningful change was defined as a ≥ 5-point mean difference from baseline and between the ZO and O arms. RESULTS: Patients were randomized to ZO (n = 145) or O (n = 72). By week 48, descriptive analysis results indicated that patients in the ZO arm demonstrated improved outcomes in role functioning and fatigue and nausea/vomiting symptoms, compared with those in the O arm. Both groups experienced improvements in pain symptoms. EQ-5D-5L VAS scores showed no observable differences between treatment arms through week 48. MMRM analysis revealed that the global health status/quality of life of patients treated with ZO improved, as did fatigue, at week 12. At week 24, patients in the ZO arm experienced a clinically meaningful improvement in role functioning, pain, and fatigue. CONCLUSIONS: In patients with R/R FL, ZO was associated with improved PROs compared with O. These findings suggest that zanubrutinib contributed clinically meaningful benefits to patient HRQoL when added to obinutuzumab. TRIAL REGISTRATION: The ROSEWOOD trial is registered on ClinicalTrials.gov (BGB-3111-212; ClinicalTrials.gov identifier: NCT03332017).
Keywords: dospělí; Humans; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; lidé středního věku; Middle Aged; Pyrimidines; mužské pohlaví; folikulární lymfom; humanizované monoklonální protilátky; Adult; pyrimidiny; Antibodies, Monoclonal, Humanized; hodnocení výsledků péče pacientem; Patient Reported Outcome Measures; ženské pohlaví; Lymphoma, Follicular; lidé; Pyrazoles; Aged; Quality of Life; senioři; Male; pyrazoly; kvalita života; Female